The Case for Commemoration Controversies in Canadian History Education - Gibson, Lindsay (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2021)
Commemorations are events or actions that honour and memorialize significant events, people, and groups from the past. In recent years there have been numerous contentious debates about commemorations of historical events and people in countries around the world, including Canada. In this article I argue that commemoration controversies should be an essential part of teaching and learning history in K–12 schools because they have the potential to be meaningful and relevant for students, they address civic education competencies central to history and social studies curricula in Canada, and they provide rich opportunities for advancing students’ historical consciousness and historical thinking. In the final section of the article I describe how six second-order historical thinking concepts can be used to invite students to think historically about commemorations.